Evidence for a second peptide cleavage in the C-terminal domain of rodent intestinal mucin Muc3. - Khatri, Ismat A (2004)
Rat intestinal mucin Muc3 (rMuc3), like its human homologue (MUC3) and several other membrane mucins, contains a C-terminally located SEA (sea urchin sperm protein, enterokinase and agrin) module, with an intrinsic proteolytic site sequence G downward arrow SIVV (where G downward arrow S is the glycine serine cleavage site). As shown previously [Wang, Khatri and Forstner (2002) Biochem. J. 366, 623-631], expression of the C-terminal domain of rMuc3 in COS-1 cells yields a V5 epitope-tagged N-terminal glycopeptide of 30 kDa and a Myc- and His epitope-tagged C-terminal glycopeptide of 49 kDa. The present study shows that the 49 kDa membrane-anchored fragment undergoes a further cleavage reaction which decreases its size to 30 kDa. Western blotting, pulse-chase metabolic incubations, immunoprecipitation and deglycosylation with N-glycosidase F were used to detect and identify the proteolytic products. Both the first and second cleavages are presumed to facilitate solubilization of Muc3 at the apical surface of enterocytes and/or enhance the potential for Muc3 to participate in ligand-receptor and signal transduction events for enterocyte function in vivo.